Reflections on nursing students’ fear and anxiety arising from clinical practicums - Cruz Araújo, Agostinho Antônio; de Godoy, Simone; Arena Ventura, Carla Aparecida; Rodolfo Silva, Ítalo; Santos de Almeida, Emerson Willian; Costa Mendes, Isabel Amélia (Investigación y Educación en Enfermería, 2024)
Background. Anxiety and fear are emotional responses that may emerge when individuals anticipate threats. Undergraduate nursing students may experience feelings of hopelessness and anguish in the clinical learning experience, directly impacting their academic performance. This study aims to reflect upon the fear and anxiety faced by nursing students during clinical training. Synopsis of Contents. Two thematic axes were focused: Students’ perception regarding preceptorship attitudes and positions; Relational teaching-learning processes and their influence on the students’ professional identity. Preceptors are expected to encourage the establishment and maintenance of good relationships in the collaborative network in which students are included, especially with the multi-professional health team, to have more comprehensive academic support. Conclusion. The role and importance of each individual in academic training, such as students and professors, is emphasized, seeking to promote positive experiences in the teaching-learning process to enable undergraduate students to more effectively develop moral sensitivity and take responsibility for patient-centered care.